2019
DOI: 10.3390/nu11020417
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Usual Serving Size of Flavanol-Rich Cocoa Powder Ingested with a Diabetic-Suitable Meal on Postprandial Cardiometabolic Parameters in Type 2 Diabetics—A Randomized, Placebo-Controlled, Double-Blind Crossover Study

Abstract: Randomized controlled trials indicate that flavanol-rich cocoa intake may improve postprandial glucose and lipid metabolism in patients with type 2 diabetes (T2D), based on studies with meals that impose a strong metabolic load. Hence, the aim of the present study was to investigate whether flavanol-rich cocoa powder ingested as part of a diabetic-suitable meal may beneficially affect glucose, lipid metabolism, and blood pressure (BP) in patients with T2D. Twelve adults with T2D, overweight/obesity, and hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
2
11
1
Order By: Relevance
“…Likewise, the consumption of a decaffeinated green tea extract providing a daily dose of 856 mg of EGCG for 16 weeks produced a significant reduction in HOMA-IR index in type 2 diabetic individuals [63]. In contrast, other studies have found that the acute and the short-term consumption of cocoa flavonoids had no effect on insulin sensitivity in diabetic patients [64][65][66][67]. Thus, supplementation with silybin-beta-cyclodextrin for 6 months tended to decrease the insulin resistance (HOMA-IR) in patients with T2D (differences were not significant) [68].…”
Section: Effects Of Flavonoids On Insulin Signaling In T2dmentioning
confidence: 98%
“…Likewise, the consumption of a decaffeinated green tea extract providing a daily dose of 856 mg of EGCG for 16 weeks produced a significant reduction in HOMA-IR index in type 2 diabetic individuals [63]. In contrast, other studies have found that the acute and the short-term consumption of cocoa flavonoids had no effect on insulin sensitivity in diabetic patients [64][65][66][67]. Thus, supplementation with silybin-beta-cyclodextrin for 6 months tended to decrease the insulin resistance (HOMA-IR) in patients with T2D (differences were not significant) [68].…”
Section: Effects Of Flavonoids On Insulin Signaling In T2dmentioning
confidence: 98%
“…HDL increased while the concentration of TC, LDL, TG, and hsCRP remained unchanged [ 92 ]. No effects could be observed after an acute supplementation of 2.5 g cacao powder (ACTICOA TM ; 40.4 mg EC) with a diabetic-suitable breakfast in hypertensive, overweight or obese subjects with T2D [ 93 ].…”
Section: Antidiabetic Effects Of Flavan-3-ols: Clinical Interventimentioning
confidence: 99%
“…The ingestion of FL-rich foods could have a significant potential for managing cardiovascular health [9][10][11] . Many intervention studies have suggested that the intake of FL results in beneficial alterations in the metabolism such as a significant decrease in plasma LDL with an increase in HDL 12,13 and rise in glucose tolerance [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%